2020
DOI: 10.1002/chem.201904938
|View full text |Cite
|
Sign up to set email alerts
|

Bimodal Heterogeneous Functionality in Redox‐Active Conjugated Microporous Polymer toward Electrocatalytic Oxygen Reduction and Photocatalytic Hydrogen Evolution

Abstract: The designing and development of heterogeneous catalysts for conversion of renewable energy to chemical energies by electrochemical as well as photochemical processes is at the forefront of energy research. In this work, two new donor–acceptor‐based redox‐active conjugated microporous polymers (CMPs) (TAPA‐OPE‐mix and TAPA‐OPE‐gly) are synthesized through Schiff base condensation reaction using a microwave synthesizer. Notably, the asymmetric and symmetric bola‐amphiphilic nature of the OPE struts results in d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 73 publications
(172 reference statements)
0
4
0
Order By: Relevance
“…To develop a CMP-based highly robust, efficient, and environmentally benign photocatalyst, we envisioned a strategy based on covalent integration of redox-active π-chromophoric building units through C–C coupling. This results in a permanently porous π-conjugated network with the ability of facile charge migration and substrate diffusion to the catalytic sites. Further, assembling of a donor–acceptor (D-A) chromophore in CMP would be an excellent approach to stimulate the photocatalytic activity of CO 2 reduction toward highly reduced product because of intramolecular charge transfer (ICT) interactions. The cumulative push–pull effect between the electron-rich donor and electron-deficient acceptor chromophore in CMP would result in facile exciton separation and corresponding charge migration to the cocatalyst surface or the substrate for efficient catalytic activity. , Additionally, the appearance of the low-energy charge transfer absorption band due to the donor–acceptor dyad will assist in absorbing visible light.…”
Section: Introductionmentioning
confidence: 99%
“…To develop a CMP-based highly robust, efficient, and environmentally benign photocatalyst, we envisioned a strategy based on covalent integration of redox-active π-chromophoric building units through C–C coupling. This results in a permanently porous π-conjugated network with the ability of facile charge migration and substrate diffusion to the catalytic sites. Further, assembling of a donor–acceptor (D-A) chromophore in CMP would be an excellent approach to stimulate the photocatalytic activity of CO 2 reduction toward highly reduced product because of intramolecular charge transfer (ICT) interactions. The cumulative push–pull effect between the electron-rich donor and electron-deficient acceptor chromophore in CMP would result in facile exciton separation and corresponding charge migration to the cocatalyst surface or the substrate for efficient catalytic activity. , Additionally, the appearance of the low-energy charge transfer absorption band due to the donor–acceptor dyad will assist in absorbing visible light.…”
Section: Introductionmentioning
confidence: 99%
“…Singh et al synthesized two donor–acceptor-based CMPs (TAPA-OPE-mix and TAPA-OPE-gly) via a Schiff base condensation reaction [ 55 ]. They observed that the asymmetric and symmetric bola-amphiphilic nature of oligo-(p-phenyleneethynylenes) (OPE) struts has resulted in not only the distinct nano-structuring and morphologies in the products, but also the different electrochemical behavior and ORR performance.…”
Section: Electrocatalytic Active Sites Pinpointed From Popsmentioning
confidence: 99%
“…Fujishima and Honda (1972) were the first to achieve UV light-assisted electrochemical water splitting by means of a TiO 2 photoanode in a photoelectrochemical cell . Subsequently, a variety of photocatalysts, ranging from inorganic materials (metal oxides, metal sulfides, metal oxy sulfides, and metal nitrides), MOFs, and porous organic polymers to crystalline COFs, have been investigated for hydrogen evolution via photocatalytic water splitting. In 2009, Wang and co-workers demonstrated that polymeric carbon nitride ( g -C 3 N 4 ), as an organic semiconductor, can generate hydrogen from water under photoirradiation even without the use of precious metals . As an impact of the semicrystalline structure and presence of triazine/heptazine moieties, carbon nitride exhibited moderate hydrogen generation performance.…”
Section: Introductionmentioning
confidence: 99%